Types of Attributive Constructions in Middle English Poetry - E. A. Nilsen; I. K. Mashko (Дискурс, 2025)
Introduction. The research focuses on attributive constructions functioning in Middle English poetic texts. The analysis of the identified attributive structures using a morphological approach is carried out. The main aim is to identify the types of attributive constructions characteristic of poetic texts of the Middle English period and describe their peculiarities.Methodology and sources. The research is carried out on the material of the original text of Geoffrey Chaucer's ‘The Canterbury Tales’ and the text of its modern adaptation, presented on the website of Harvard University. The total volume of the investigated fragment of the original text is 6105 words. Attributive constructions were selected in accordance with the classification proposed by V.L. Kaushanskaya. The final corpus of attributive constructions was obtained using the method of continuous sampling and totalled 396 unique attributive constructions. At the second stage of the study, quantitative analysis of the identified attributive constructions was carried out in order to determine their percentage ratio in the text fragment selected for analysis.Results and discussion. The most frequent type of attributive construction is the model in which the role of the attribute is performed by the adjective (37 %). The least frequent are the types of attributive constructions in which the attribute is expressed by: 1) a noun in the nominative case (≈ 1 %); 2) a numeral (≈ 1 %). The vast majority of the identified constructions belong to the prepositional type (70 %).Conclusion. The analysis of attributive constructions based on the material of poetic texts of the Middle English period shows that the attribute could be expressed: 1) by an adjective; 2) by a possessive pronoun or noun in the genitive case; 3) using constructions with a prepositional group. As for the position of the attribute relative to the core of the construction, in addition to the prepositive and postpositive types characteristic of Modern English, a number of “exceptions” were identified in G. Chaucer’s “Canterbury Tales” in which the conventional type of the attribute relative to the core is reversed, which reflects the specifics of the Middle English language, which was experiencing a period of rapid development and cardinal changes in the structure of language on the way to the formation of the literary norm. Further studies on the evolution of types and peculiarities of attributive constructions based on the material of Middle English and Early Modern English poetry seem extremely promising.